Colesevelam a bile acid sequestrant use in type 2 diabetes mellitus as glucose and lipid lowering agent - SAA, Hasan; C, Shobha (Indian Journal of Pharmacy Practice)
The bile acid sequestrants are the group of medications utilized to bind certain components of bile in the gastrointestinal tract. Enterohepatic circulation of bile acids is disrupted by sequestering bile acids and preventing their reabsorption from the gut. They are generally considered as hypolipidemic agents, although may be used for purposes other than cholesterol lowering. In diabetes lipid abnormality occur leading to various other cardiovascular complications. Studies have demonstrated that changes in enterohepatic circulation modulate FXR- and TGR5-mediated pathways may regulate glucose homeostasis. This review discusses the major findings of clinical studies which have investigated the glucose and lipid lowering effects of Colesevelam for the treatment of Type 2 Diabetes Mellitus (Type 2 DM) and the mechanism involved in regulating lipid and glucose metabolism through bile acid mediated activation of FXR and TGR 5 signaling pathways.
Keywords: Colesevelam; Type 2 DM; FXR; TGR5